Optoelectronic Synapses Based on MXene/Violet Phosphorus van der Waals Heterojunctions for Visual-Olfactory Crossmodal Perception - Ma, Hailong; Fang, Huajing; Xie, Xinxing; Liu, Yanming; Tian, He; Chai, Yang (Nano-Micro Letters, 2024)
The crossmodal interaction of different senses, which is an important basis for learning and memory in the human brain, is highly desired to be mimicked at the device level for developing neuromorphic crossmodal perception, but related researches are scarce. Here, we demonstrate an optoelectronic synapse for vision-olfactory crossmodal perception based on MXene/violet phosphorus (VP) van der Waals heterojunctions. Benefiting from the efficient separation and transport of photogenerated carriers facilitated by conductive MXene, the photoelectric responsivity of VP is dramatically enhanced by 7 orders of magnitude, reaching up to 7.7 A W−1. Excited by ultraviolet light, multiple synaptic functions, including excitatory postsynaptic currents, paired-pulse facilitation, short/long-term plasticity and “learning-experience” behavior, were demonstrated with a low power consumption. Furthermore, the proposed optoelectronic synapse exhibits distinct synaptic behaviors in different gas environments, enabling it to simulate the interaction of visual and olfactory information for crossmodal perception. This work demonstrates the great potential of VP in optoelectronics and provides a promising platform for applications such as virtual reality and neurorobotics. Highlights: 1 The photoelectric response of violet phosphorus (VP) is significantly enhanced by the MXene/VP van der Waals heterojunctions and the highest photoresponsivity of VP is demonstrated. 2 The first VP-based optoelectronic synapse with essential synaptic behaviours is demonstrated. 3 Proof-of-concept visual-olfactory crossmodal perception based on MXene/VP optoelectronic synapses is explored to mimic neuromorphic vision with multi-sensory interactions.